Rola cyrkulacji atmosfery w kształtowaniu wielkości zachmurzenia ogólnego na Spitsbergenie (1983-2013) = The role of atmospheric circulation in shaping total cloudiness over Spitsbergen (1983-2013) - Lipiński, Oskar; Łupikasza, Ewa (IGiPZ PAN, 2016)
The main island of the Svalbard Archipelago, Spitsbergen, is located in the centre of the Atlantic sector of the Arctic and is exposed to an increased dynamic of change in weather conditions, the shaping of which is affected by specific synoptic situations. In the work described here, it was the impact of atmospheric circulation on cloudiness over Spitsbergen that was studied, by reference to (1983-2013) average daily values for cloudiness at the Ny-Ålesund, Svalbard Lufthavn and Hornsund Meteorological Stations. The influence of atmospheric circulation was examined on the basis of a simplified Calendar of synoptic situations for Spitsbergen (Niedźwiedź, 2013), whose classification embraces 5 cyclonic, 5 anticyclonic and 1 undetermined type. The average daily values for cloudiness referred to provided the basis for further calculations of annual, monthly and seasonal values, with results then being presented in relation to the course over years and seasons, as conditioned by the amount of sunlight reaching Spitsbergen at different times of the year. The analysis thus took in the polar day, the polar night and two much shorter (spring and autumn) transition periods, which are of somewhat different lengths at the several different stations. Annual courses for the proportions of days capable of being regarded as characteristic were then described, while a final stage to the work concerned the relationship between cloudiness and the eleven aforementioned types of atmospheric circulation. Average values for sky cover with different circulation types were calculated, as were the conditional probabilities relating to the occurrence of the characteristic days. The results demonstrate that, notwithstanding environmental conditions, atmospheric circulation plays an important role in cloud formation over the whole island. However, despite the relatively short distances involved, the stations analysed were found to be characterised by significant differences where the spatial distribution of values for levels of sky cover by cloud were concerned. The causal relationship between cloudiness and respective circulation types is not as important as the direction of advection of air masses. The highest mean daily cloudiness values were reported in circulation types entailing advection from the south, i.e. Sc+SWc and Sa+SWa (relating to both cyclonic and anticyclonic types). Lowest average levels of cloudiness co-occurred under the Na+NEa and Nc+NEc circulation types. The total number of characteristic days at particular stations is also quite varied. Ny-Ålesund reports the most cloudless days (N=0%) and clear days (N<20%) during the year. The same is true of the number of completely overcast days (N=100%). The largest number of cloudy days (N>80%) characterises Hornsund, the most southerly of the stations on Spitsbergen studied. At Svalbard Lufthavn, average cloudiness during the polar night is greatest when the air flow originates in the north. The greatest variation in the distribution of cloudiness is to be observed during the polar night (at Svalbard Lufthavn and Ny-Ålesund) or in the autumn transitional period (Hornsund).
24 cm
Keywords: total cloudiness; atmospheric circulation; Sptisbergen; Arctic